Nonmedullary thyroid carcinoma in kindreds: A case series and review of familial papillary thyroid carcinoma - Rajavelu, Narayanan (Indian Journal of Case Reports, 2024)
Papillary thyroid carcinoma (PTC) is the most common thyroid cancer, comprising approximately 85% of cases. Familial PTC (FPTC) accounts for 5–10% of papillary thyroid carcinoma (PTC) cases and often presents more aggressively with higher rates of lymph node metastasis, distant spread, and recurrence. In this report, a 53-year-old man was diagnosed with a Hurthle cell predominant nodule with a focus on papillary carcinoma following a routine checkup and family history revealing three first-degree relatives with PTC. He underwent a total thyroidectomy which was managed with thyroxine and regular follow-up. His 46-year-old wife, in a consanguineous marriage, also opted for evaluation due to the family history. Ultrasound and fine-needle aspiration cytology revealed multifocal papillary carcinoma, leading to total thyroidectomy and similar management with thyroxine. The report highlights the clinical significance of recognizing FPTC in families with multiple affected members, stressing that early intervention can minimize the need for extensive surgery, including lymph node dissection and radioactive iodine therapy. By identifying FPTC early, clinicians can improve outcomes, reduce recurrence rates, and tailor treatment to avoid more invasive procedures, emphasizing the need for proactive management in familial thyroid cancer cases.